Elimination of Ferromagnetic Particles Aggregation for Investigation by Electron Microscopy - О.S. Kuzema; P.O. Kuzema (Журнал нано- та електронної фізики)
It has been described the device for sample preparation of highly dispersed ferromagnetic powders including micropowders for permanent magnets, magnetic carriers, machine and mechanism components’ wear products contained in lubricants for investigation of these materials by light and electron microscopy. The device eliminates the coalescence of ferromagnetic particles and improves reliability of the results of such objects investigation. The technique of such device application has been described and exemplified for various materials investigation.